Comparing two cordless impression techniques for dimensional accuracy: An in vitro study - Nupur Dabas; Monika Malik Vigarniya; Shefali Phogat; Reshu Madan; Puja Malhotra; Ashish Dabas (Wolters Kluwer Medknow Publications, 2018)
Introduction: For a successful fixed partial prosthodontics, obtaining an accurate impression for making an accurate cast is of prime importance. Aim: The study emphasizes on using modified impression techniques for fixed prosthodontics without using retraction cord. Various mechanical and chemical methods have been used for achieving gingival retraction. Most of them are expensive, time consuming and uncomfortable for the patient. Cordless impression procedures using conventional impression materials are alternative to these methods. Methodology: In the present study, two cordless fixed prosthodontic impression procedures, matrix impression system and prefabricated crown shell technique; have been described and compared in terms of dimensional accuracy.An articulated acrylic resin typodont prepared with reference points was used as a master model. Addition silicon impression materials in various consistencies were used for making impressions. The coordinate measurement machine (Llyod,Germany) was used for three dimensional measurement of master model and stone casts with an accuracy of 0.0001mm. Observations: When comparing the accuracy of casts as per statistical analysis Group B (prefabricated crown shell technique) casts were less accurate in relation to inter abutment distance whereas all other distances produced statistically insignificant mean deviation from the master model. Conclusion: It can be concluded that prefabricated crown shell technique is not recommended for a long span bridge framework but is well indicated while making cordless impressions for fabrication of single crown.